Network Externalities in a Dynamic Monopoly - Raimondello Orsini; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2002)
We reconsider the role of network externalities in a dynamic spatial monopoly where the firm must invest in order to accumulate capacity, while consumers may have either linear or quadratic preferences. We (i) characterize saddle poin equilibria, (ii) prove that the extent of market coverage is increasing in the network effect and (iii) unlike the existing static literature on the same problem, the monopolixt may not make introductory price offers. Then, we briefly dea with the socially optimal solution, showing that, in general, a planner would serve more consumers than a profit-seaking monopolist.
Keywords: 330